PENGARUH MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR KOGNITIF PESERTA DIDIK DI SEKOLAH DASAR - Yuni Indriyani; Salsabila Fitri Rizkika Junaedi (STKIP Subang, 2022)
The improvement of cognitive learning outcomes can be influenced by several factors, one of which is the use of audio-visual media. This study aims to determine the differences in cognitive learning outcomes of students who are subject to the use of audio-visual media and students who are not subject to the use of audio-visual media, as well as to determine the influence of the use of audio-visual media on improving cognitive learning outcomes of students. This research is a Quasi-Experimental study. This research was carried out at SD Pertiwi in grade IV with a population of 66 students. The sampling technique used is a nonequivalent control group design with class IV A (control class) as many as 25 students and class IV B (experimental class) as many as 25 students. The data collection technique used is a test. The tests used are in the form of pretests and posttests to take data on cognitive learning outcomes. Data management techniques are carried out using normality tests, homogeneity tests, independent sample t test, and simple linear regression test. The results of this study show that: 1) There are differences in cognitive learning outcomes between students who use audio-visual media and students who do not use audio visual media based on the results of the independent sample t test obtained a Sig. value (2-tailed) of 0.226 > 0.05. 2) There was a significant influence of the use of audio-visual media on improving the cognitive learning outcomes of students based on the results of the simple linear regression test obtained a calculated t value of 2.432 > t table 2.069 which means that Ho was rejected and H???? was accepted.